Short term negative effect of oxalic acid in Apis mellifera iberiensis - Martin Hernandez, R.=700 1 Higes, M.; Perez, J.L.; Nozal, M.J.; Gomez, L.; Meana, A.
(Es, En)
Ilus., 19 ref.
Keywords: ABEJA MELIFERA; TOXICIDAD; ACIDO OXALICO; LESIONES; ESPAÑA